2019
DOI: 10.1016/j.bbrep.2019.100655
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of MUC2 due to a decrease in the expression of lectins and apoptotic defects in colitis patients

Abstract: Introduction The involvement of mucin, lectin, and apoptosis in colitis is still unclear. This study aimed to investigate changes in MUC2 expression, inflammation, and changes in lectin expression in colitis patients. Methods A total of 17 patients were divided into two groups including 11 hemorrhoid patients as a control group and 6 colitis patients. MUC2 mutation analysis was carried out using immunofluorescent and FISH techniques. Assessment of caspase-3, Ki-67, NF-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The examination of colon specimens from UC patients indicated that MUC2 expression significantly decreased compared to that from healthy individuals [72] . The mucus layer was also revealed to become thinner and even absent in some parts, independent of local inflammation [ 73 , 74 ], and the inner mucus layer of patients with active UC is reported to be more penetrable [ 74 , 75 ].…”
Section: Detection Of Muc2 Mucus Barrier Dysfunction Intestinal Bacterial Invasion and Dysbiosis During Uc Development Clinically And Manmentioning
confidence: 98%
“…The examination of colon specimens from UC patients indicated that MUC2 expression significantly decreased compared to that from healthy individuals [72] . The mucus layer was also revealed to become thinner and even absent in some parts, independent of local inflammation [ 73 , 74 ], and the inner mucus layer of patients with active UC is reported to be more penetrable [ 74 , 75 ].…”
Section: Detection Of Muc2 Mucus Barrier Dysfunction Intestinal Bacterial Invasion and Dysbiosis During Uc Development Clinically And Manmentioning
confidence: 98%
“…Muc2 degradation of LS174T cell surface by Amuc_1434* was detected by immunofluorescence staining [31,57]. LS174T cells (10 6 cells/mL) were cultured on 6-well tissue culture plates at 37 • C overnight.…”
Section: Muc2 Immunofluorescencementioning
confidence: 99%
“…Mucins are glycoproteins present in mucus, and gel‐forming mucins, namely, muc5ac‐ like and muc5d ( muc2‐ like), were significantly altered in zebrafish fed soya bean. During intestinal inflammation in humans, muc2 was downregulated because of apoptotic defects (Wibowo et al., 2019). An upregulation of muc5ac in the intestine cells of humans by food‐derived peptides has been reported previously (Martínez‐Maqueda et al., 2012).…”
Section: Discussionmentioning
confidence: 99%